Effects of nitrogen and phosphorus imbalance input on rhizosphere and bulk soil bacterial community of Suaeda salsa in the Yellow River Delta - Zhang, Zehao; Sun, Jingkuan; Li, Tian; Shao, Pengshuai; Ma, Jinzhao; Dong, Kaikai (Frontiers in Marine Science, 2023)
The effects of nitrogen (N) and phosphorus (P) addition on soil microbial diversity have been widely studied, however, the response of bacterial community to N and P imbalance input remains unclear. Using a high-throughput Illumina Miseq sequencing platform, N and P imbalance addition experiment was conducted to characterize the rhizosphere and bulk soil bacterial community of Suaeda salsa (S. salsa) in the Yellow River Delta. The results showed that the rhizosphere soil bacterial community α-diversity was significantly higher than bulk soil. The rhizosphere soil Bacteroidetes and Actinobacteria were higher and lower than bulk soil, respectively. N and P imbalance input had small effects on the composition and α-bacterial diversity of the rhizosphere soil, while significantly increasing the bulk soil bacterial diversity and remarkably changing the community composition. Differences in the response of rhizosphere and bulk soil bacterial community to N and P imbalance input were caused by soil organic matter (SOM) content. The N and P imbalance input increased the relative abundance of bulk soil Eutrophic bacteria and decreased the relative abundance of the predicted oligotrophic bacteria (Acidobacteria, Chorolflexi). Rhizosphere and bulk soil bacterial community α-diversity was significantly correlated with SOM, salt, total carbon (TC) and total N (TN) content, with SOM and salt having the greatest effect on bulk soil bacterial community composition. There may be a threshold N-P input ratio between 15:1 and 45:1. This threshold is the optimal ratio for increasing the diversity of bacterial community.